Host transcriptome profiling for resistance against lumpy skin disease (LSD) - Mohammad Hossein Banabazi; Steven Van Borm; Tomas Klingström; Adnan Niazi; Kris De Clercq; Laurent Mostin; Andy Haegeman; Dirk Jan de Koning (BMC Research Notes)
Abstract Objective Lumpy skin disease (LSD) is an acute or subacute systemic viral disease of cattle that shows variation in the response of cattle to LSD virus infection. To better understand the mechanisms underlying this response diversity in field studies and under carefully controlled artificial infections, we studied the differentially expressed genes (DEGs) between two resilient versus three susceptible Holstein bulls before an infection challenge and three time points after that. Results The host transcriptome profiling revealed that IL1RAP gene expression could be a potential determinant in distinguishing between resilient and susceptible cattle (padj < 0.05). It was significantly shifted from up-regulated prior to infection to down-regulated three days post-infection in the LSD-resilient cattle. Its expression remained up-regulated among the susceptible cattle post-infection compared to pre-infection. The results showed that seven days post-infection may be a critical time point for LSD infection. The Gene Ontology (GO) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment test showed a few enriched GO terms and pathways relevant to the LSD and the involvement of the IL1RAP gene. This pilot study, with limited statistical power, is the first to investigate bovine gene expression profiling in response to LSDV.